Novel glitazone attenuates rotenone-induced toxicity in mouse model of Parkinson’s disease - Ankith B. Shetty, Kamsagara Linganna Krishna, Bommenahally Ravanappa Prashantha Kumar, Hittanahalli Shivakumar Nandini (Journal of Applied Pharmaceutical Science, 2021)
Parkinson’s disease (PD) is the second most common neurodegenerative disorder, and there are no drugs that will directly tackle the inflammatory component of PD. In the present study, we assessed the novel glitazone for reversal of rotenone-induced toxicity in experimental mouse model. The 14 virtual glitazone compounds were subjected to molecular docking study for target protein 3CS8; among these, compound C25 and C34 have shown better binding activity. Pharmacokinetics studies were conducted for the above compounds in rat model to chose best one for further toxicity and efficacy studies. The compound C25 showed better kinetic profile when compared to C34 and better t1/2 when compared to the standard pioglitazone. Compound C25 then tested for acute toxicity by OECD guideline 423 and evaluated for its neuroprotective activity in mouse model. The activity of the compound was assessed by the behavioral parameters on weekly intervals during the study period and estimated the antioxidant level in the brain homogenate. The compound has shown good activity dose-dependently; however, further research is required to confirm its activity and to support our hypothesis.
Keywords: 3CS8, docking, PPARÝ, glitazones, Parkinsonism, kinetics.